Report of the Delaware Criminal Law Recodification Project - Kussmaul, Matthew (2017)
In 1973, during the “first wave” of American criminal law recodification efforts following the publication of the Model Penal Code, Delaware adopted a new criminal code. While it represented a dramatic improvement over the law it replaced, its initial clarity and utility were greatly diminished by subsequent piecemeal legislation. Delaware’s current criminal code is lengthy, inconsistent, and replete with duplicative and outdated offenses that impose disproportional punishments. This process of criminal code deterioration is not unique to Delaware and plagues other U.S. jurisdictions. In 2015, however, stakeholders in Delaware’s criminal justice system initiated a code revision process, commissioning the authors to draft a Proposed Code and commentary to address these issues, and resulting in this Report. By utilizing modern code drafting techniques and other innovations, the Proposed Code comprehensively, yet concisely, states the rules governing criminal liability in Delaware in a way that is easy to read and understand, and responds to twenty-first-century challenges and norms. While focusing on Delaware, the Proposed Code also illustrates how modernized criminal codes could be drafted for other jurisdictions, and can serve as a stimulus and a model for a “second wave” of American criminal law recodifications.The Proposed Code’s primary goals are to ensure proportional punishment and eliminate inconsistencies in current law. To further these objectives it relies on various methods. For instance, it utilizes general grade adjustments – such as felony recidivism, hate crimes, and offenses committed against vulnerable persons – to increase the maximum punishment for any offense in the Special Part. Yet, it carefully limits the number of adjustments that can be applied to a single offense. The Proposed Code also keeps basic offense definitions simple, by regularly employing offense-specific grading provisions to demarcate additional offense elements (in addition to using them to specify maximum punishment). This dual function of grading provisions is also instrumental for consolidating multiple offenses, or degrees of offenses. For instance, the Proposed Code’s assault section consolidates nearly a dozen current law offenses (including three degrees of assault), many of which overlap and conflict. In addition to these methods, the Proposed Code uses numerous substantive and structural code drafting innovations. For example, the Code refines the distinctions between defenses, affirmative defenses, general defenses, and exceptions to liability. Some “affirmative defenses” in current law are actually general defenses, and have been treated as such in the Proposed Code; others have been appropriately converted into exceptions. The remainder has been re-labeled simply as “defenses,” serving the same function as in current law, but without its ambiguities. The Proposed Code also provides a comprehensive index of defined terms in a single section. Each term’s substantive definition, however, appears at the end of the Chapter that either introduces or most heavily relies upon it. Taken together, these features aid in locating and using the Proposed Code’s definitions. Besides, the Code employs descriptive headings, and organizes offense and defense elements using subsections as much as practicable, thereby enhancing readability. Additionally, the Proposed Code attends to contemporary problems not envisioned by current law. For example, the Code addresses present-day activities such as “sexting,” and prevents the unintended possibility of their prosecution as child pornography (a serious felony), limiting liability to a low level misdemeanor. The Code also dispenses with current law’s references to conflicting distributive principles of deterrence, incapacitation and rehabilitation among its “general purposes.” In combination with the Proposed Code’s focus on proportional grading, this approach is consistent with modern criminal law theory and the first amendment to the Model Penal Code in 2007 that defined desert as its primary distributive principle. Notably, the Code also introduces a novel approach to minimum mandatory punishments, requiring that the predicate offense be committed with at least “knowing” culpability (in addition to other factors, such as relatively high grades and defined categories of offenses). In effect, this requirement “splits” individual offenses requiring lower levels of culpability such as recklessness, and applying minimum punishment only if the offenses were committed knowingly or intentionally. This Report consists of two Volumes. Volume 1 begins with an executive summary, followed by a detailed explanation of the project’s history, the principles guiding the drafting of the Proposed Code, and illustrations of these principles’ function in the context of Delaware criminal law. The heart of Volume 1 is the text of the Proposed Code itself. The final part of Volume 1 contains a Summary Grading Table that groups all offenses covered by the Proposed Code according to their grade, and assists in the evaluation of the Proposed Code’s proportionality judgments. It also contains two “conversion tables” that allow the reader to see how current law relates to the proposed provisions. Volume 2 contains extensive commentary explaining each section of the Proposed Code and addressing the proposed disposition of current law. The authors hope that this Report will prove useful for scholars engaged in recodification projects and jurisdictions considering criminal code revisions. (Subsequent political discussions in Delaware have since altered the proposed Delaware code from what is contained herein.